2013
DOI: 10.1021/ja309763f
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Study of the Diels–Alder Reaction of Paramagnetic Endohedral Metallofullerene: Reaction of La@C82 with 1,2,3,4,5-Pentamethylcyclopentadiene

Abstract: The reaction mechanism of the Diels-Alder reaction of paramagneticendohedral metallofullerene, La@C82, and 1,2,3,4,5-pentamethylcyclopentadiene was studied theoretically and experimentally. Theoretical calculations revealed that this reaction proceeds via a concerted mechanism that includes formation of a stable intermediate. The activation energy of a retro-Diels-Alder reaction was also studied experimentally, which is in good agreement with theoretical results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
41
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 61 publications
3
41
0
Order By: Relevance
“…For paramagnetic EMFs, the electronic spin resonance (ESR) technique is a powerful tool to detect the spin distributions and spin–nucleus couplings on internal species192021. By means of ESR, it was revealed that the magnetic property of the internal species can be roughly manipulated by changing the dynamic movement of internal species.…”
mentioning
confidence: 99%
“…For paramagnetic EMFs, the electronic spin resonance (ESR) technique is a powerful tool to detect the spin distributions and spin–nucleus couplings on internal species192021. By means of ESR, it was revealed that the magnetic property of the internal species can be roughly manipulated by changing the dynamic movement of internal species.…”
mentioning
confidence: 99%
“…To explain the selectivity in the DA reaction of La@C 2v (9)-C 82 , DFT calculations were performed. 119 It is noteworthy that La@C 2v (9)-C 82 is a paramagnetic molecule. Recently, DFT studies predicted that the reaction between 1,3-butadiene radical cation with ethylene proceeds via a stepwise path involving an open chain intermediate.…”
Section: Sbclmentioning
confidence: 99%
“…123 The absorption spectra of the resulting fulleropyrrolidines were similar to that of La@C 2v (9)-C 82 (Cp*), implying that the addition sites were identical to that of La@C 2v (9)-C 82 (Cp*). 119 However, the lack of singlecrystal XRD data has made the structural determination for the La@C 2v (9)-C 82 -based fulleropyrrolidines uncertain to date.…”
Section: Sbclmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15] Generally, the classic D-A cycloadditions are reacted by electronic-decient diene and electronic-rich dienophile synergetically. [16][17][18][19] However, there are a series of untraditional D-A reactions [20][21][22][23][24][25][26][27][28][29][30][31] between electronically mismatched components, such as the addition between 1,3-butadiene and ethylene (both electron-decient components) or trans-1,3-butadiene and C60 or C70 (both electron-rich components). This novel D-A reaction always exhibits excellent selectivity but also requires stricter conditions than those of the traditional D-A reaction, where the components of dienes and dienophiles generally experience different transformations in order to satisfy the requirement of D-A reaction through the formation of free radical ions, 20,21 molecular electrical reversal [22][23][24][25] and polarity reversal.…”
Section: Introductionmentioning
confidence: 99%